The Linking Education and Knowledge on BPJS Participant Collectibility and Satisfaction: A Structural Equation Modeling Analysis - Aswar, Nurul Fadilah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to investigate the relationship between education and health knowledge, specifically in terms of service quality and premium amount, in the context of BPJS health in Makassar, using participant satisfaction as a mediating variable. This study employs a quantitative methodology, utilizing structural equation modeling (SEM) based on Smart-PLS. We collected data by administering questionnaires to 100 BPJS Kesehatan participants. We collected data by distributing online questionnaires through the Google Forms platform to participants who satisfied the research criteria. We conducted inferential statistical analysis using structural equation modeling (SEM) with the assistance of Smart-PLS analysis software. The results of the study indicate that there is a relationship between the education and knowledge of BPJS participants and their utilization of health services. Service quality has a significant effect on the level of collectibility and participant satisfaction. Higher service quality, such as efficiency, responsiveness, and professionalism, increases participant satisfaction, which in turn increases payment compliance. In addition, although the premium amount does not directly affect the level of collectibility, it significantly affects participant satisfaction. Perceived fair or affordable premiums enhance satisfaction, thereby mediating the influence on collectibility.